2009
DOI: 10.1002/clc.20502
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Variant and Microvascular Angina

Abstract: Prinzmetal's variant angina (VA) and cardiac syndrome X (CSX) are two distinct, usually easily recognizable, forms of angina syndromes, caused by epicardial spasm, usually responsible for transient transmural myocardial ischemia at rest and by coronary microvascular dysfunction (CMVD), usually responsible for effort induced subendocardial ischemia, respectively. In this article we report clinical evidence in three patients of the simultaneous occurrence of angina episodes typical of both VA and CSX, suggesting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 26 publications
1
4
1
Order By: Relevance
“…Previous studies have shown that a reduced vasodilatory capacity of the coronary microcirculation can lead to exercise-induced angina in CSX [3] and recent observations indicate that some CSX patients may share features of Prinzmetal's variant angina [5,6]. In contrast, our study showed that distal and diffuse epicardial as well as increased microvascular constriction in response to acetylcholine can be an important pathogenic mechanism in patients with CSX.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…Previous studies have shown that a reduced vasodilatory capacity of the coronary microcirculation can lead to exercise-induced angina in CSX [3] and recent observations indicate that some CSX patients may share features of Prinzmetal's variant angina [5,6]. In contrast, our study showed that distal and diffuse epicardial as well as increased microvascular constriction in response to acetylcholine can be an important pathogenic mechanism in patients with CSX.…”
Section: Discussioncontrasting
confidence: 81%
“…In the absence of coronary artery disease, coronary microvascular dysfunction, mainly abnormal vasodilation, has been proposed as a pathogenic mechanism in at least a proportion of patients [3,4]. However, recent clinical observations suggest that an increased coronary vasoconstrictor response may have a pathogenic role in CSX [5,6]. Moreover, studies have consistently shown that a proportion of CSX patients have not only exertional chest pain but also rest angina [7,8].…”
Section: Introductionmentioning
confidence: 98%
“…Of note, in agreement with these data, in 3 patients with typical VA, we have recently reported clinical evidence of the simultaneous occurrence of angina episodes typical of both VA and microvascular angina, suggesting that some common pathogenetic mechanisms may be responsible for clinical manifestations of both functional macro- and microvascular coronary artery abnormalities in some angina patients [26]. …”
Section: Discussionsupporting
confidence: 67%
“…In some patients, spasm may even be present in the coronary epicardial arteries as well as in the microvessels. 8 Anatomically, epicardial coronary spasm is defined as focal if it is confined within the borders of a coronary segment according to the 16 segment coronary model of the American Heart Association. 9 Diffuse spasm is present if adjacent coronary segments are involved.…”
Section: Definition and Pathophysiology Of Coronary Artery Spasmmentioning
confidence: 99%